PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE FINANCIAL PERFORMANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Studi pada Bank Umum Syariah di Indonesia) - Maulidan Maulidan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2015)
AbstractThe purpose of this research is to examine the influence of good corporate governance and corporate financial performance on corporate social responsibility. The data used in this study is secondary data. Samples were taken by purposive sampling method sample size obtained was 24 syariah general bank companies listed in bank Indonesia 2011-2013 . The analysis technique used is multiple linear regression using SPSS 20.The study uses independent variable good corporate governance, corporate financial performance and dependent variable corporate social responsibility. the results of this study indicate that the simultaneous testing (F-test), variable good corporate governance, corporate financial performance have a significant influence on corporate social responsibility. in a partial test (T-test), variable good corporate governance size a have a significant influence on corporate social responsibility. while the variable corporate financial performance have no influence on corporate social responsibility. Keyword: good corporate governance, corporate financial performance, and corporate social responsibility.